ANALISIS PENGETAHUAN WANITA USIA SUBUR (WUS) DENGAN TINGGINYA TINGKAT PENGGUNAAN KONTRASEPSI SUNTIK - Widaningsih, Ida; Larasati, Lytha; Hardiyanti, Masitoh (Jurnal Delima Harapan, 2025)
Background: Knowledge or cognitive domain is a very important domain in shaping a person's actions. Knowledge included in the cognitive domain has six levels, namely knowing, understanding, application, analysis, synthesis, and evaluation. Objective: To analyze the knowledge of women of childbearing age (WUS) with high levels of use of injectable contraception at TPMB Masitoh Hardiyanti Method: This study combines quantitative and qualitative approaches to provide a more comprehensive understanding of the observed phenomenon. The number of samples in this study was 173 respondents. Data analysis using the Chi-Square Test. Results: The results of the Chi-Square test obtained a value of p = 0.001 <0.05 for age, p = 0.021 <0.05 for education, p = 0.001 <0.05 for work, p = 0.014 <0.05 for sources of information and p = 0.000 <0.05 for family support. This means that there is a relationship between age, education, work, sources of information and family support with the knowledge of women of childbearing age (WUS). Conclusion: all independent variables (Age, Education, Occupation, Information Sources and Family Support) with knowledge of women of childbearing age (WUS) about injectable contraception. It is expected to provide information on the characteristics of injectable contraception acceptors and become evaluation material for health workers to provide counseling.